Study on Temperature Deformation of Thrust Bearing Plate - LI Yong-hai; LI Xiao-guang; LAI Feng; SUN Xiang-zhi; ZHAO Qian-ni (Journal of Harbin University of Science and Technology)
The temperature field of oil film on the surface of the thrust bearing is obtained according to the lubrication theory，and regarded as the temperature of the surface of mirror plate． The deformation caused by temperature of thrust plate is simulated by using finite － element numerical analysis method，and focuses on the loading method and the loading process of temperature field of thrust plate． The analysis results show that the thermal deformation caused by temperature difference between thrust plate and the mirror plate deformation is large， and the deformation presents as downward convex along the radial direction